Anthropomorphic service recovery: the panacea following service failure of automated CSAs - Nobukhosi Dlodlo (Acta Commercii)
Orientation: Automated customer service agents (CSAs) are not mere tools but social interaction entities with anthropomorphic traits capable of predicting consumer responses following unique online service failures scenarios.